PENGEMBANGAN GAMIFIED LEARNING: SOLUSI MENGATASI DEMOTIVASI DAN MENINGKATKAN KEMAMPUAN BERFIKIR TINGKAT TINGGI (HOTS) MAHASISWA DALAM ILMU SHOROF - Abdul Ghofur; Siti Durotun Naseha; Sri Widoyoningrum (Universitas Islam Negeri Mataram, 2025)
This research aims to develop gamified learning as a solution to overcome demotivation and enhance higher-order thinking skills (HOTS) among students in learning Ilmu Shorof, one of the branches of linguistics that is often considered difficult and boring. Gamification introduces game elements that can boost students' motivation, engagement, and critical thinking skills. This study employs a Research and Development (R&D) method using the ASSURE model, which includes six steps: learner analysis, objective formulation, method and media selection, media utilization, learner participation, and evaluation and revision. The developed product was validated by subject matter, media, and language experts. The trial subjects consisted of 50 Arabic Language Education (PBA) students from Hasyim Asy'ari University, with a questionnaire used to measure students' perceptions of the product, particularly in terms of increasing motivation and HOTS. The study resulted in a web-based software called